The impact of the coronavirus disease 2019 pandemic on elective urological procedures in Australia - Athul John; Mustafa Mian; Subhashaan Sreedharan; Arman A. Kahokehr (Asian Journal of Urology)
Objective: To investigate the changes in elective private urological procedures in Australia during the coronavirus disease 2019 pandemic. Methods: Data were extracted from publicly available datasets from Medicare Benefits Schedule using item numbers assigned to each commonly performed urological intervention. These procedures were divided into three groups: Oncological therapeutic, diagnostic, and non-oncological therapeutic procedures. A smoothing model, based on the historic procedure numbers from 2017 to 2019, was used to forecast monthly number of procedures performed in each category between January 2020 and June 2020. These forecasted models were compared with reported figures. Results: A total of 108 169 procedures were performed between January 2020 and June 2020 based on the Medicare Benefits Schedule item numbers listed. There was a significant reduction (percentage change) in total procedures performed in April 2020 (−22.6%, 95% confidence interval [CI]: −28.7% to −15.4%) and May 2020 (−33.2%, 95% CI: −37.5% to −28.3%). There was a significant reduction in oncological therapeutic, non-oncological therapeutic, and diagnostic procedures performed in April 2020 and May 2020 (p<0.05). These numbers did not include procedures performed in public sector. Conclusion: There was a significant reduction in total urological procedures (including diagnostic, oncological, and non-oncological) performed in months of April 2020 and May 2020 during time of federal restrictions. Both public and private healthcare sectors need to be supported in the upcoming months to prevent further delays in treatment and poorer clinical outcomes.